Evaluating full lemmatization of Croatian texts - Agić, Željko (Array, 2009)
The chapter presents the implementation and evaluation of a module for full lemmatization of Croatian texts. The module implements several lemmatization procedures, all of them based on merging outputs of the previously developed stochastic morphosyntactic tagger CroTag and the infectional lexicon of Croatian. Evaluation of the lemmatization module on two test cases, simulating realistic and ideal operating conditions, provided full lemmatization accuracy scores of 96.96 and 98.15 percent on a newspaper corpus, respectively. It is also shown that a majority of errors in this framework, 57.14 percent in the realistic testing scenario, occur on word forms with external homography. Moreover, approximately 80 percent of all lemmatization errors occur on nouns, adjectives, verbs and adverbs in that particular order. Language resources, testing environment and procedure descriptions are provided in the paper along with a discussion of obtained results and possible future research directions.